Fabrication of honeycomb‐structured protein arrays via one‐step method. Issue 8 (8th October 2018) - Ju, Yuanlai; Ding, Lingyun; Zhu, Jiafeng; Sun, Wei
ABSTRACT: "Inverse emulsion"‐"breath figures" (Ie‐BF) method was introduced for fabricating porous films with protein arrays decorating the interior of the obtained polymeric pores. Compared with the traditional BF method in which only hydrophobic or amphiphilic components could be used, Ie‐BF method created a system with water phase carrying water‐soluble protein before solution casting, which makes it possible to obtain patterned protein arrays within the BF structure in one‐step. The stability of the inverse emulsion system is an intractable problem solved by high shearing emulsification. Experimental parameters, including the concentration of the matrix polymer, water/oil ratio of the IE, amount of both emulsifier and protein in IE, were evaluated for establishing an optimal condition to prepare fine BF arrays by following the Ie‐BF method. Proteins tagged with fluorescein isothiocyanate were added into the emulsion to cast films, and pores efficiently enriched by proteins were revealed by the images of fluorescence microscope, indicating the successful preparation of protein arrays. Among all the approaches of establishing patterned structures of biomacromolecules, Ie‐BF shows promising potential in future applications. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2019, 136, 47084. Abstract :